Bi-paratopic and multivalent VH domains block ACE2 binding and neutralize SARS-CoV-2 - Bracken, Colton J.; Lim, Shion A.; Solomon, Paige; Rettko, Nicholas J.; Nguyen, Duy P.; Zha, Beth Shoshana; Schaefer, Kaitlin; Byrnes, James R.; Zhou, Jie; Lui, Irene; Liu, Jia; Pance, Katarina; et al. (Nature chemical biology, 2021)
Neutralizing agents against SARS-CoV-2 are urgently needed for the treatment and prophylaxis of COVID-19. Here, we present a strategy to rapidly identify and assemble synthetic human variable heavy (VH) domains toward neutralizing epitopes. We constructed a VH-phage library and targeted the angiotensin-converting enzyme 2 (ACE2) binding interface of the SARS-CoV-2 Spike receptor-binding domain (Spike-RBD). Using a masked selection approach, we identified VH binders to two non-overlapping epitopes and further assembled these into multivalent and bi-paratopic formats. These VH constructs showed increased affinity to Spike (up to 600-fold) and neutralization potency (up to 1,400-fold) on pseudotyped SARS-CoV-2 virus when compared to standalone VH domains. The most potent binder, a trivalent VH, neutralized authentic SARS-CoV-2 with a half-maximal inhibitory concentration (IC 50 ) of 4.0 nM (180 ng ml −1 ). A cryo-EM structure of the trivalent VH bound to Spike shows each VH domain engaging an RBD at the ACE2 binding site, confirming our original design strategy. A screening approach finds VH-domain antibodies that bind the SARS-CoV-2 Spike protein receptor-binding domain at its interface with host ACE2. Bi-paratopic and multivalent binders have high affinity and potency.